The trigonometric way

Geometry Level 3

Given that 5 ( 1 x + 1 + x ) = 6 x + 8 1 x 2 5(\sqrt{1-x}+\sqrt{1+x}) = 6x+8\sqrt{1-x^2} , find the value of x x .

23 25 \frac{23}{25} 49 50 \frac{49}{50} 24 25 \frac{24}{25} 47 50 \frac{47}{50}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Surya Prakash
Aug 15, 2015

Observe that for the validity of the given equation, x < 1 |x| < 1 .

So, Let x = c o s ( 2 θ ) x= cos(2 \theta ) .

The expressions changes to

5 2 ( c o s θ + s i n θ ) = 6 c o s 2 θ + 8 s i n 2 θ 5\sqrt{2} (cos \theta + sin \theta) = 6 cos 2\theta + 8 sin 2 \theta 1 2 ( c o s θ + s i n θ ) = 3 5 c o s 2 θ + 4 5 s i n 2 θ \dfrac{1}{\sqrt{2}}(cos \theta + sin \theta) = \dfrac{3}{5} cos 2 \theta + \dfrac{4}{5} sin 2 \theta

Let, s i n α = 3 5 sin \alpha = \dfrac{3}{5} . So, the above expression reduces to

s i n ( π 4 + θ ) = s i n ( α + 2 θ ) sin(\dfrac{\pi}{4} + \theta ) = sin( \alpha + 2 \theta)

π 4 + θ = 2 θ + α \dfrac{\pi}{4} + \theta = 2 \theta + \alpha

θ = π 4 α \theta = \dfrac{\pi}{4} - \alpha

Now,

x = c o s ( 2 θ ) = c o s ( π 2 2 α ) = s i n ( 2 α ) x= cos (2 \theta) = cos ( \dfrac{\pi}{2} - 2 \alpha ) = sin (2 \alpha) = 2 s i n ( α ) c o s ( α ) = 2 × 3 5 × 4 5 = 24 25 = 2 sin(\alpha) cos (\alpha) =2 \times \dfrac{3}{5} \times \dfrac{4}{5} = \boxed{\dfrac{24}{25}} .

Moderator note:

Great usage of the trigonometric substitution to simplify the expression!

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...